The ESO Diffuse Interstellar Bands Large Exploration Survey EDIBLES: I. Project description, survey sample and quality assessment - Cox, Nick L.J.; Cami, Jan; Farhang, Amin; Smoker, Jonathan; Monreal-Ibero, Ana; Lallement, Rosine; Sarre, Peter J; Marshall, Charlotte C.M.; Smith, Keith T.; Evans, Christopher J.; Royer, Pierre; Linnartz, Harold; et al. (EDP Sciences, 2017)
The carriers of the diffuse interstellar bands (DIBs) are largely unidentified molecules ubiquitously present in the interstellar medium (ISM). After decades of study, two strong and possibly three weak near-infrared DIBs have recently been attributed to the C+ 60 fullerene based on observational and laboratory measurements. There is great promise for the identification of the over 400 other known DIBs, as this result could provide chemical hints towards other possible carriers. In an effort to systematically study the properties of the DIB carriers, we have initiated a new large-scale observational survey: the ESO Diffuse Interstellar Bands Large Exploration Survey (EDIBLES). The main objective is to build on and extend existing DIB surveys to make a major step forward in characterising the physical and chemical conditions for a statistically significant sample of interstellar lines-of-sight, with the goal to reverse-engineer key molecular properties of the DIB carriers.